ANALISA MODEL GETARAN MAIN ENGINE PADA KAPAL - Kurnia Putra Iwan; Wirawan Husodo Adi; Abu Jamiin M. (Politeknik Perkapalan Negeri Surabaya, 2018)
This article mainly describes vibration on ship’s main engine foundation. The high amplitude of vibration could damage ship’s hull structure and disturb ship’s passenger. The amplitude can be reduced by avoiding resonance between natural frequency and exciting frequency. Thereby in this article, the domain frequency is identified from Bode Diagram-based vibration source. A modelling from vibration data used as a reference to analyze domain frequency from vibration source. In data modelling a method called ARMA is used to determine the best model from every nodes main engine foundations, and then the model is analyzed using Bode Diagram. The first point of Bode Diagram’s results shows natural frequency of main engine foundation in the amount of 402 rad/s, 1360 rad/s, and 4120 rad/s on phase 180°, The second point of Bode Diagram’s results shows natural frequency of main engine foundation in the amount of 15.8 rad/s, 561 rad/s, 1760 rad/s, and 4010 rad/s on phase 180°, The third point of Bode Diagram’s results shows natural frequency of main engine foundation in the amount of 2140 rad/s and 9840 rad/s on phase 180°, and the fourth point of Bode Diagram’s results shows natural frequency of main engine foundation in the amount of 8260 rad/s on phase 180°.